The role of type 2 diabetes mellitus on hypertensive‐related aortic stiffness. Issue 6 (19th February 2018) - Sciatti, Edoardo; Vizzardi, Enrico; Castiello, Assunta; Valentini, Francesca; Bonadei, Ivano; Gelsomino, Sandro; Lorusso, Roberto; Metra, Marco
Abstract : Background: Hypertension is strongly related to arterial stiffness in a cause‐effect fashion. Diabetes mellitus is also thought to determine vascular damage, mostly by means of advanced glycosylation end‐products (AGEs). Aim of our study was to study the role of type 2 diabetes mellitus (T2DM) as regard ascending aortic elastic properties in hypertensive patients. Methods: We prospectively enrolled outpatients with hypertension (n = 99) and type 2 diabetes mellitus plus hypertension (n = 42) without cardiovascular events. They underwent a transthoracic echocardiography to measure aortic diameters, aortic elastic properties (ie, compliance, distensibility, stiffness index, Peterson's elastic modulus, pulse wave velocity, M‐mode strain), tissue Doppler imaging (TDI) to calculate diastolic (Eʹ and Aʹ) and systolic (Sʹ) velocities, and tissue strain. Multivariable analysis was run to assess the association between T2DM and these variables after correcting for possible confounders (age, sex, body mass index [BMI], dyslipidemia). Results: The two groups did not differ as regards age, sex, BMI, and blood pressure. However, T2DM patients were more likely to be dyslipidemic (43% vs 71%, P  = .003). Aortic diameters were similar in the two groups, but the aortic elastic properties significantly more impaired in T2DM group. At multivariable analysis, stiffness index, Peterson's elastic modulus, the TDI waves, and the tissue strain remained associated with the co‐presence of T2DM and hypertension. Conclusion: Our data suggest that people suffering from both T2DM and hypertension have more impaired aortic elastic properties than those hypertensive alone. Considering the prognostic role of aortic stiffness, these patients may benefit from a closer follow‐up.